2023
DOI: 10.7717/peerj.14810
|View full text |Cite
|
Sign up to set email alerts
|

Using eDNA sampling for species-specific fish detection in tropical oceanic samples: limitations and recommendations for future use

Abstract: Background Over the past decade, environmental DNA (eDNA) has become a resourceful tool in conservation and biomonitoring. Environmental DNA has been applied in a variety of environments, but the application to studies of marine fish, particularly at tropical latitudes, are limited. Since many commercially important Caribbean fishes are overexploited, these species are optimal candidates to explore the use of this method as a biomonitoring tool. Specifically, for many of these species, the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…An increasing number of studies have shown that the amount of eDNA is not only related to the presence of a species but also to its abundance [9,10]. Previous studies have confirmed a positive correlation between eDNA and biomass in various aquatic environments [11], including ponds, lakes, rivers, streams and oceans [10,12,13].…”
Section: Introductionmentioning
confidence: 98%
“…An increasing number of studies have shown that the amount of eDNA is not only related to the presence of a species but also to its abundance [9,10]. Previous studies have confirmed a positive correlation between eDNA and biomass in various aquatic environments [11], including ponds, lakes, rivers, streams and oceans [10,12,13].…”
Section: Introductionmentioning
confidence: 98%